Interpretation of adjoint sensitivity analysis for shape optimal design of electromagnetic systems. Issue 8 (1st November 2015) - Lee, Hyang‐beom; Ida, Nathan
Abstract : An interpretation of the meaning of the adjoint system and its variable, as used in the process of shape optimal design of electro‐magnetic systems with sensitivity analysis is introduced. Sensitivity formulae for the discrete and continuum approach are compared and the meaning of the adjoint system is discussed. The adjoint system simplifies sensitivity calculations, and provides the link between the objective function and design variables.